The science and technology of civil engineering materials - Young, J. Francis (Prentice Hall international series in civil engineering and engineering mechanics, 1998)
Innovative in approach, this book is a comprehensive, integrative exploration of the science and technology of construction materials that begins with a section on the structure and mechanical properties of materials. Begins with a discussion of the structure of materials (at a microscopic level), moves through mechanical properties, and follows-up with sections dealing individually with specific construction materials. A source of information for beginning and practicing civil engineers.